Catheter-based closure of aortic and mitral paravalvular leaks: existing techniques and new frontiers. (2nd September 2018) - Joseph, Timothy A.; Lane, Colleen E.; Fender, Erin A.; Zack, Chad J.; Rihal, Charanjit S.
ABSTRACT: Introduction : Significant paravalvular leak (PVL) complicates between 6% and 15% of valve replacements and can result in heart failure and hemolysis. Paravalvular leak can be effectively treated with repeat surgery; however, these procedures are associated with significant operative morbidity. Percutaneous PVL closure is increasingly being utilized as the first line therapy for symptomatic patients, but efficacy may be limited by the lack of dedicated closure devices. Areas covered : This article will review the etiology and prevalence of PVL, discuss outcomes with surgical closure, describe the mounting data supporting percutaneous interventions, and highlight areas for future research emphasizing the need for new dedicated closure devices. Expert commentary : Percutaneous PVL closure can be safely accomplished in the majority of patients with PVL thereby avoiding the risks associated with repeat surgical intervention. However, percutaneous interventions are associated with higher rates of persistent leakage in part due to off-label use of devices intended for other applications. Efforts to develop devices specifically intended for PVL closure are needed to further improve outcomes for percutaneous PVL closure.